INNOVATION IN NEW STUDENT ADMISSION MANAGEMENT BASED ON INFORMATION TECHNOLOGY AND PAID PROMOTION AT AS-SYIFA BOARDING SCHOOL, SUBANG - Rustandi, Feri; Wahid, Dul; Fitri, M. Zein; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the innovation in New Student Admission Management (PPDB) at As-Syifa Boarding School Subang. The research focuses on the application of information technology and digital systems as modern approaches to the PPDB process. The utilization of technology has proven to enhance the efficiency of the admission process by saving time and resources while reducing the risk of manual errors. Furthermore, improved transparency and accessibility at every stage of the admission process have been achieved, offering a more positive experience for prospective students and their parents. To reach prospective students from various regions across Indonesia and even abroad, As-Syifa effectively implements paid promotion strategies. Promotions are conducted through various popular social media platforms. Creative promotional content successfully captures the attention of the target audience. This strategy is supported by local and international networks, broadening the scope of promotion and strengthening the institution's image. A rigorous selection process is applied to ensure that only students meeting high passing scores are admitted, with consideration of academic achievements, character values, and leadership potential. This study concludes that innovations in PPDB management, through the use of information technology and effective promotional strategies, have a significant impact on improving the quality of prospective student admissions.